Mercury concentration in tissues of a captive green turtle (Chelonia mydas L.) - Bezerra, Moisés F. (2014)
Mercury (Hg) residence time in the ocean varies from approximately 30 years in the surface (0-200 m) layer to a century in the intermediate and deep water zones (UNEP 2013). During this period, Hg can be absorbed by marine biota, recycled in the water column and eventually transported to deep layers and deposited in sediments. Therefore, long-lived oceanic organisms, such as sea turtles, are exposed throughout their lives to the legacy of Hg pollution from anthropogenic sources of the Anthropocene as well as from long-term emissions from natural sources.[...]